Acute effects of exposure to 1 mg/m(3) of vaporized 2-ethyl-1-hexanol in humans - Ernstgård, L; Norbäck, D; Nordquist, T; Wieslander, G; Wålinder, R; Johanson, G (Indoor air, 2010)
The objective was to assess acute effects from controlled exposure of volunteers to 2-ethyl-1-hexanol, a volatile organic compound that is often found in indoor air. Sixteen males and fourteen females were in random order exposed to 1 mg/m(3) of vapors of 2-ethyl-1-hexanol or to clean air (control exposure) in an exposure chamber during 2 h at rest. The subjects performed symptom ratings on Visual Analog Scales. During exposure to 2-ethyl-1-hexanol subjective ratings of smell and eye discomfort were minimally but significantly increased. Ratings of nasal irritation, throat irritation, headache, dyspnoea, fatigue, dizziness, nausea, and intoxication were not significantly affected. No exposure-related effects on measurement of blinking frequency by electromyography, measurement of the eye break-up time, vital staining of the eye, nasal lavage biomarkers, transfer tests, spirometric and rhinometric measures were seen. No differences in response were seen between sexes or between atopics and non-atopics. Practical Implications It is important to assess acute effects in volatile organic compounds like 2-ethyl-1-hexanol. 2-ethyl-1-hexanol is often found in indoor air generated by degradation of plastic building materials or in new buildings. There are associations between 2-ethyl-1-hexanol in indoor air and respiratory effects, eye irritation, headache, and blurred vision. A controlled chamber exposure study in acute effects was performed. In conclusion, this study showed weak subjective symptom of irritation in the eyes.